Adipose-Derived Stem Cells (ASCs) for Regeneration of Intervertebral Disc Degeneration: Review Article - Romaniyanto, FNU (Taylor & Francis, 2022)
The intervertebral disc (IVD) is an important structure in the human body because it functions as a weight-bearing. This structure undergoes a process of degeneration like the rest of the body and this process is known as intervertebral disc degeneration (IDD) which is the most common cause of low back pain (LBP). The current common management, either conservative or surgical, is pain-relieving and has not been able to restore degenerated disc optimally. Changes in the IVD microenvironment in IDD conditions make it difficult for the regeneration process to occur. Research to reverse the degeneration process continues to develop, one of them is the use of adipose-derived stem cells (ASCs). ASCs is superior due to the ability to differentiate into several other cells such as adipocytes, chondrocytes, and osteoblasts, it also has ability to act as immunomodulators by stimulating the migration of immune cells to damaged tissues. ASCs becomes a good choice because it is easy to obtain, low donor site morbidity, high proliferation rate, and excellent differentiation abilities. Research on the optimal preparation process for ASCs and their application to various disorders continues to advanced. This study aims to review the potential use of ASCs for regeneration of intervertebral disc degeneration.